Divide and Conquer: Split CP Hypothesis in Rhetorical Questions, the Case of SFPs in RQs - Tulling, Maxime (Student Undergraduate Research E-journal!, 2015)
Sentence final particles (SFPs) like Dutch hè and hoor add speaker-related information to sentences. Despite the fact that SFPs are not typically allowed in content-questions, particles like hè occur in rhetorical questions (RQs), while SFPs like hoor cannot. Here I propose that this is due to two factors: (i) RQs are different from ordinary questions, with the former only allowing for the answer the speaker believes is true, and (ii) SFPs operate at different ‘structural levels’. Particles like hè convey a similar meaning as RQs, making them compatible, while SFPs like hoor function at a different level, incompatible with RQs.